Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Seismic response of tunnels adjacent to saturated fault zones under SV-wave: Effects of fluid-solid coupling and fault properties - Ming-Yu Chang; Yu-Quan Liu; Yu-Sheng Shen; Wei Zheng; Yang Yu; Ming-Chao Yan; Yong-Yi Li (Tunnelling and Underground Space Technology, 2026)

Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

A chiral metal-organic cage Al-CMOC for high-resolution gas chromatographic separation - Xiao-Fang Shu; An-Xu Ma; Fu Li; Chang-Xiu Ma; Jin Liu; Xu-Xu Jin; Sheng-Ming Xie; Bang-Jin Wang; Jia-Ni Yang; Jun-Hui Zhang; Li-Ming Yuan (Analytica Chimica Acta, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

A room temperature activatable highly-conductive liquid metal ink and its flexible electrohydrodynamic printing - Xu Chen; Yiwen Feng; Kaiwen Chen; Zhenya Wang; Gengyuan Li; Chang Liu; Shulei Zheng; Chumeng Zhang; Zefei Li; Xiangji Chen; Xiaopeng Zhang; Ran Zhang; et al. (Chemical Engineering Journal, 2026)

GHK-Cu enabled Zn-CaP biomimetic coating on titanium promotes immunomodulation driven vascularized osseointegration - Tong Sun; Chao Liu; Xinyao Liu; Guodong Zhao; Guowen Duan; Dongbiao Chang; Lulu Han; Mingyang Ma; Kunyue Zhang; Jun Sheng; Jiaojiao Yang; Xingyu Chen; et al. (Chemical Engineering Journal, 2026)

Aquaculture-relevant florfenicol exposure causes hepatopancreatic bioaccumulation and metabolic-immune toxicity in the mud crab Scylla paramamosain - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Zhi-Long Chen; Xin-Jian Liu; Zhi-Xun Guo (Environmental Pollution, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

USP35-mediated NRF2 deubiquitination attenuates experimental cryptorchidism-induced testicular damage and H2O2-induced apoptosis and oxidative stress in spermatogonia - Xiang Liu; Jing-Jing Sun; Chang-Kun Mao; Yong-Sheng Cao; Qi-Fei Deng; Guang-Yuan Li (Molecular and Cellular Biochemistry, 2026)

Outcome-specific park-catchment assessment of age-supportive neighborhood parks using field audits and street-view imagery - Li-Chih Ho; Yu-Sheng Shen; Sin-Rou Fu; Po-Ju Chang (Landscape and Ecological Engineering, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Baicalin alleviates repeated superovulation induced ovarian dysfunction and oocyte impairment by suppressing excessive glycolysis - Lin-Feng Li; Hao Shen; Zhi-Min Qi; Tian Luo; Sheng-Ming Liu; Li-Li Ou; Chang-Long Xu; Yu Liu (Theriogenology, 2026)

Reprogramming senescent granulosa cells for germ-cell generation - Dai Heng; Kairang Jin; Guoxing Yin; Chenglei Tian; Xiaoyan Sheng; Jiangtao Lu; Yiwei Wu; Xiaoying Ye; Panpan Shi; Huiyu Li; Chang Liu; Lin Liu; et al. (Science China Life Sciences, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Experimental study on dynamic response of a calcareous seabed around a trenched pipeline under non-linear wave–current loading - Zuodong Liang; Dajun Liu; Lin Cui; Mengxiao Li; Zheng Wang; Dayu Chang; Hailun Chen; Ke Sun; Jisheng Zhang; Dong-Sheng Jeng (Ocean Engineering, 2026)

The role of water in REE mineralization of carbonatite systems: constraints from apatite and biotite volatiles - Jian-Hui Su; Xin-Fu Zhao; Johannes Hammerli; Sheng-Ren Chang; Xiao-Chun Li; Wen-Lei Song; Mei-Fu Zhou (Geochimica et Cosmochimica Acta, 2026)

Experimental study of thermo-mechanical properties of binary PCM-fiber composite energy piles - Hong Chang; Huicheng Jiang; Yunjie Li; Yuan Du; Xing Wu; Zhaoxuan Wang; Sheng Jiang; Zhengheng Gan (Energy and Buildings, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Association of plasma n-3 polyunsaturated fatty acid with gut mycobiome and implications for glucose homeostasis - Congmei Xiao; Yue Xi; Xinyu Wang; Chang Gao; Ruiqi Shi; Zelei Miao; Yuhui Liang; Wanglong Gou; Ke Zhang; Chun Wang; Xinxiu Liang; Meng Ye; et al. (Science China Life Sciences, 2026)

Age- and season-modulated water use strategies in mixed plantations of Betula alnoides and Castanopsis hystrix - Yu-han Chang; Bo-yao Chen; Chun-sheng Wang; Kai-li Liu; Hai-feng Yin; Jie Zeng (Agricultural and Forest Meteorology, 2026)

A Bimodal Graph Neural Network with Transfer Learning and Contrastive Learning for Protein-Protein Interaction Site Prediction - Sheng Chang; Boyan Zhang; Changbo Li; Fan Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Scalable dry-processing of ceramic-polymer composite flexible passive daytime radiative cooling films - Zhongyin Tian; Kai Zhang; Xiangyu Tong; Sheng Lu; Yongchao Yu; Yiqian Zhou; Hsiang-Shun Chang; Yan Feng; Yunzhi Li; Xiaowen Chen; Guangyu Yang; Shihang Li; et al. (Chemical Engineering Journal, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Antisolvent temperature engineering enables rapid nucleation for efficient red perovskite light-emitting diodes - Tao Sheng; Jie Guo; Gang Wang; Miao Zeng; Yulin Mao; Shaohui Liu; Jike Zhang; Gu Li; Peiyuan Pang; Jiale Chang; Ying Chen; Dejian Yu; et al. (Chemical Engineering Journal, 2026)

Experimental Study of the Combined Action of Random Waves and Current Induced Hydrodynamics and Seabed Response Around a Protective Three-Dimensional Pipeline - Dayu Chang; Risheng Wang; Wenqi Si; Mengxiao Li; Zheng Wang; Dajun Liu; Ke Sun; Dong-Sheng Jeng; Lin Cui; Dejian Wei (Journal of Marine Science and Engineering, 2026)
Submarine pipelines serve as the primary transportation infrastructure for offshore energy resources and are becoming increasingly important in modern industrial and domestic applications. A series of laboratory experiments on the dynamic seabed response of three-dimensional pipeline-seabed systems under random wave and current conditions was conducted. The results demonstrate as follows: (1) Under the combined action of random waves and ambient currents, the wave profiles in the vicinity of the submarine pipeline exhibit distinct irregular and nonlinear characteristics; (2) Compared with random waves acting alone, the superposition of random waves and currents modifies wave propagation behavior: a co-directional current enhances wave propagation, whereas a countercurrent suppresses it; (3) For a pipeline subjected to the three-dimensional random waves, pore-pressure amplitude decreases with increasing wave-incidence angle. Specifically, maximum values corresponding to incidence angles of 30° and 45° are generally lower than those at 0° and 15°, at a seabed depth of z/d = 0.0938, and the value at an incident angle of 45 degrees attenuates by 21.31% compared to that of 0°; (4) Coarse sand exhibits weaker pore-pressure attenuation than fine sand around the three-dimensional pipeline-seabed scheme, indicating that sediment grain size exerts a substantial influence on seabed response; (5) The protective effect of geotextile and stone is more obvious, whereas PVC is limited to the front and underside of the pipe. The deeper the seabed, the smaller the effect of protective measures. For reproducibility, the test matrix covered wave-incidence angles α = 0°, 15°, 30°, and 45°, irregular-wave conditions with H1/3 = 0.08–0.14 m and T1/3 = 1.2–1.8 s, and currents U = –0.2 m/s at a constant still-water depth h = 0.45 m.

Dietary carbohydrate fuels a metabolic strategy for osmotic adaptation, enhancing growth and resilience of Litopenaeus vannamei in low-salinity water - Zhao Li; Zhi Luo; Sheng-Wei Lin; Feng-Lu Han; Chang Xu; Er-Chao Li (Aquaculture International, 2026)

Integrated Multi-Endpoint Analysis of Soluble Copper(II) Chloride–Induced Oxidative Stress, Mitochondrial Dysfunction, and Genotoxicity in RAW264.7 Macrophages - Ping-Kun Tsai; Sheng-Wen Wu; Yen-Ju Lee; Yu-Ting Chang; Shiuan-Shinn Lee; Yung-Chuan Ho; Li-Chiu Yang; Yu-Hsiang Kuan (Biological Trace Element Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Unveiling Mo doping effects in hydrated vanadium oxide cathodes for high-energy zinc-ion batteries: Evidence from operando synchrotron X-ray and DFT analysis - Sanna Gull; Hsu-Chen Cheng; En-Hao Li; Tsung-Yi Chen; Chung-Sheng Ni; Wan-Ju Yu; Hao-Hsiang Chang; Ai-Yin Wang; Ruey-An Doong; Chin-Lung Kuo; Yu-Chun Chuang; Bo-Hao Chen; et al. (Chemical Engineering Journal, 2026)

Mud crab reovirus infection disrupts the intestinal microbiota and intestinal physiological homeostasis in mud crabs (Scylla paramamosain) - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Xin-Jian Liu; Zhi-Long Chen; Zhi-Xun Guo (Aquaculture, 2026)

Environmentally adaptive self-healing hydrogels via multiscale control of water molecules for human-machine interaction - Liping Li; Yang Yang; Wanhui Shi; Yunzhen Chang; Ying Zhang; Wenjing Hou; Sheng Zhu; Gaoyi Han (Chemical Engineering Journal, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

Oxymatrine Alleviates Cerebral Ischemia/Reperfusion Injury By Targeting HDAC1 to Regulate Mitochondria-Related Autophagy and Oxidative Stress - Chang-Sheng Ma; Bo Han; Yu-Xi Liu; Chang-Ku Shi; Dong-Lun Li; Jin-Fen Guo; Min Bai; Shu-Chen Meng; Li-Ying Zhang; Meng-Yuan Duan; Mao-Tao He (Molecular Neurobiology, 2026)
Oxymatrine (OMT), a major alkaloid extracted from Sophora flavescens, has been widely recognized for its anti-inflammatory and anti-cancer properties. However, its precise neuroprotective mechanisms in cerebral ischemia/reperfusion (I/R) injury remain to be fully elucidated. In this study, we combined in vivo and in vitro models to investigate the therapeutic effects of OMT on cerebral I/R injury and glutamate-induced neuronal toxicity during the reperfusion process. In vivo, a mouse middle cerebral artery occlusion (MCAO) model was established to recapitulate I/R injury, whereas glutamate-exposed HT22 hippocampal neurons were utilized as an in vitro model to mimic excitotoxic damage. Bioinformatics analysis, integrated with molecular docking, identified histone deacetylase 1 (HDAC1) as a potential direct target of OMT. Subsequent experimental validation demonstrated that OMT attenuates I/R-induced brain damage by modulating HDAC1-mediated pathways involved in autophagy and oxidative stress regulation. OMT treatment significantly reduced infarct volume and improved neurological function in mice. At the cellular level, OMT suppressed mitochondrial apoptosis and reactive oxygen species (ROS) accumulation, restored mitochondrial membrane integrity, and rebalanced mitochondrial dynamics by downregulating fission-related proteins (Fis1) and upregulating fusion markers (Mfn2). Additionally, OMT inhibited excessive autophagy through modulation of the PINK1/Parkin signaling pathway, as evidenced by decreased expression of LC3-II/I ratio, PINK1, Parkin, and NBR1, along with restored levels of P62.These findings suggest that OMT exerts its neuroprotective effects in cerebral I/R injury by targeting HDAC1, thereby alleviating oxidative stress and excessive autophagy. This study provides new mechanistic insights and supports OMT as a promising therapeutic candidate for ischemic stroke treatment. Graphical Abstract

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Characterizing maize starch gelatinization by Low-Field NMR spectroscopy - Li Ding; Samira Ebrahimi; Xingxun Liu; Staffan Persson; Jacob Judas Kain Kirkensgaard; Kasper Enemark-Rasmusse; Jinhui Chang; Sheng Chen; Andreas Blennow; Tomasz Pawel Czaja; Yuyue Zhong (Carbohydrate Polymers, 2025)

Luminescence dating of lava-baked sediments constraints on the high frequency of Holocene eruptions in the Tengchong volcanic field, southwestern China - Chang Huang; Chunxin Wang; Anchuan Fan; Sheng-Hua Li (Science China Earth Sciences, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Experimental Study on Seabed Stability Around an Offshore Pipeline Under Waves and Currents: Local Scour and Pore-Water Pressure - Mengxiao Li; Dong-Sheng Jeng; Lin Cui; Zuodong Liang; Zheng Wang; Dajun Liu; Dayu Chang; Ke Sun (Journal of Marine Science and Engineering, 2025)
Offshore pipelines are commonly used for the transportation of oil and gas from offshore to near-shore facilities in the oil and gas industry. In ocean environments, the wave- and current- induced pore-water pressure within the seabed, and the associated seabed liquefaction and local scour around pipelines, are widely recognised as among the key factors in the design of offshore pipelines. In this paper, a series of wave flume experiments were carried out on the three-dimensional (3D) scouring around a pipeline. In the experiment, in addition to the measurement of hydrodynamic characteristics and local scour, the pore-water pressure within a sandy seabed was measured. Both waves and currents were considered with different incident angles to the pipeline. This study focuses on the relationship between the variation in pore-water pressure and the development of the scouring process around the pipeline, as well as the evolution of the 3D scouring morphology near the pipeline. The experimental results show that the pore-water pressure exhibits significant changes (up to 12.5% of P0) in the beginning stage of the scouring process, especially in the area below the pipeline, where the influence of scouring on pore-water pressure is most obvious.

Utilization of water/waste engine oil emulsion for the preparation of chemical additives-free coal slurry - Keke Zhao; Jun Chen; Mingtao Chang; Fujun Sheng; Chuanxian Li; Guangyu Sun; Fei Yang; Bo Yao (Fuel, 2025)

Defining a Triassic carbonatite-related Mo-(REE) metallogenic belt along the southern margin of the North China Craton - Sheng-Ren Chang; Xin-Fu Zhao; Jian-Hui Su; Shao-Rui Zhao; Li-Ping Zeng; Carl Spandler (Mineralium Deposita, 2025)

Streptococcus atopica sp. nov., Isolated from the Feces of a Toddler with Atopic Dermatitis - Chin-Kan Chan; Hui-Shan Wu; Li-Jyun Tsai; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yi-Sheng Chen (Current Microbiology, 2025)

Hypothetical analysis of ground deformation and its effects on archaeological sites of the Silk roads with SBAS-DInSAR: An exploratory application in Xi'an City, China - Meng Zhu; Liang Tao; Fulong Chen; Xiaochen Zhou; Wei Zhou; Xun Yao; Xiaohuan Xi; Wenbo Li; Jianyang Chang; Hongqiang Li; Sheng Gao (Journal of Applied Geophysics, 2025)

The role of potassium in lode gold mineralization: insights from ab initio molecular dynamics and geochemical modeling - Gao-Hua Fan; Jian-Wei Li; Yuan Mei; Si-Yu Hu; Ri-Chen Zhong; Chang Yu; Xiao-Dong Deng; Hao Cui; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Multiscale yttrium-stabilized pillaring and fluorinated interphase engineering enable fast Mn redox toward 5C-level layered sodium oxide - Yuanyuan Liu; Qiwen Ran; Wanyue Sheng; Hanxiao Chang; Rui Cao; Jintao Liu; Mingqi Li; Xingquan Liu; Sridhar Komarneni (Chemical Engineering Journal, 2025)

Proteome Profiling of Serum Reveals Pathological Mechanisms and Biomarker Candidates for Cerebral Small Vessel Disease - Yun-chao Wang; Hang-hang Zhu; Liu-Chang He; Ya-ting Yao; Lei Zhang; Xin-li Xue; Jing-yi Li; Li Zhang; Bo Song; Chang-he Shi; Yu-sheng Li; Yuan Gao; et al. (Translational Stroke Research, 2025)

Plant community‐dominating species can sustain population biomass by modifying and strengthening their own growth traits to deal with long‐term grazing - Yu-Wen Zhang; Ze-Chen Peng; Zhao-Feng Wang; Sheng-Hua Chang; Yu-Feng An; Duo-Cai Li; Fu-Jiang Hou; Ji-Zhou Ren (Agriculture, Ecosystems & Environment, 2025)

A new method for motion-blurred object recognition in infrared remote sensing using temperature waveforms - Qinghong Sheng; Chang Yin; Bo Wang; Xiao Ling; Jun Li; Yang Du (International Journal of Remote Sensing, 2025)

Online multi-view multispectral detection for early bruised apple - Jia-Yong Song; Ze-Sheng Qin; Chang Ma; Li-Feng Bian; Chen Yang (Biosystems Engineering, 2025)

Membrane-enhanced methanogenesis efficiency and biomass retention in EGSB-AnMBR for food waste press filtrate treatment - Haojie Qin; Jianmin Liu; Wendong Chao; Jianyong Liu; Sheng Chang; Chang-Tang Chang; Tiago Martins; Yu-You Li; Hui Cheng (Environmental Research, 2025)

Antidiabetic constituents of Kaempferiae rhizoma: Previously undescribed O-linked diarylheptanoid dimers promoting GLP-1 secretion via PKA-CREB pathway - Sheng-Li Wu; Tian Wang; Xin-Yu Li; Pianchou Gongpan; Xiao-Yan Huang; Yun-Bao Ma; Chang-An Geng (Phytochemistry, 2025)

Melanoidins from stir-frying Atractylodes Macrocephala: Structural characterization, molecular weight distribution, and polyphenol delivery mechanism - Wei Li; Yajie Zhang; Xiaoxiao Wang; Yanqing Zhang; Chang-jiang-sheng Lai; Junbo Xie (Food Chemistry, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Characterization of different high amylose starch granules. Part III: How starch fine structures affect retrogradation and formation of type 3 resistant starch - Li Ding; Jiyu Yang; Jacob Judas Kain Kirkensgaard; Kasper Enemark-Rasmussen; Jinhui Chang; Lude Zhang; Sheng Chen; Andreas Blennow; Yuyue Zhong (Carbohydrate Polymers, 2025)

Biotransformation: a novel approach for the production of 6-hydroxyluteolin 7- O -methylglucuronide compound with antioxidant and anti-inflammatory potential - Chien-Yu Wu; Muddasir Khan; Hsiou-Yu Ding; Tzi-Yuan Wang; Yi-Xuan Li; Chun-Wei Liu; Jiumn-Yih Wu; Te-Sheng Chang (Natural Product Research, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

The functional role of arbuscular mycorrhizal fungi in enhancing soil organic carbon stocks and stability in dryland - Meng-Ying Li; Wei Wang; Hai-Hong Yin; Yinglong Chen; Muhammad Ashraf; Hong-Yan Tao; Shi-Sheng Li; Wen-Ying Wang; Chang-Lang Yang; Yun-Li Xiao; Li Zhu; You-Cai Xiong (Soil and Tillage Research, 2025)

Benchmarking of analysis tools and pipeline development for nanopore long-read metagenomics - Kai Peng; Yunyun Gao; Chang’an Li; Qiaojun Wang; Yi Yin; Muhammad Fazal Hameed; Edward Feil; Sheng Chen; Zhiqiang Wang; Yong-Xin Liu; Ruichao Li (Science Bulletin, 2025)

Polymetallic Te-rich melts contribute to efficient enrichment and precipitation of Au in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ri-Chen Zhong; Sarah A. Gleeson; Zhuo-Sen Yao; Daniel E. Harlov; Xiao-Dong Deng; Hao Cui; Chang Yu; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Organic-phosphate hybrids with colorful persistent luminescence - Tuo-Yu Zhou; Qian Zhao; Hong-Yu Zhao; Chang Li; Fang-Yuan Zeng; Jingjing Zhou; Jiuyuan Li; Yujiao Wang; Guang-Yue Li; Yuejuan Liang; Yanmin Song; Sheng-Hua Li (Chemical Engineering Journal, 2025)

Unlocking China's grain yield potential: Harnessing technological and spatial synergies in diverse cropping systems - Zhen-Zhong Dai; Sen Chang; Guo-Rong Zhao; Jia-Jia Duan; Hao-Yuan Liang; Zhi-Yuan Zhu; Sheng-Li Liu; Yong-Zhong Feng; Xing Wang (Agricultural Systems, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

A study on the visualization of ultrasound-assisted thawing process of frozen carrots using an in-situ schlieren imaging system - Chang Ma; Ze-Sheng Qin; Jia-Yong Song; Li-Feng Bian; Chen Yang (Innovative Food Science & Emerging Technologies, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Low-Frequency Sweep Design—A Case Study in Middle East Desert Environments - Yong-fei Qi; Zhou-hong Wei; Ming-tao Nie; Guo-fa Li; Tao Wang; Hai Ling; Sheng-kui Cong; Xin-yang Chen; Chang-ping Duan; Yang Liu (Applied Geophysics, 2025)

Xanthan gum modulation of octenyl succinic anhydrate starch-based high internal phase emulsions: Characterization, rheological behavior, and 3D printing applications - Zifan Teng; Xuerong Huang; Chi Zhang; Xiao Liu; Yingkai Li; Chang-Sheng Wang; Xingxun Liu; Fengwei Xie (Food Chemistry, 2025)

Impact of different continuous fertilizations on the antibiotic resistome associated with a subtropical triple-cropping system over one decade - Jin Zheng; Ya-Ying Li; Yu-Sheng Lu; Dan Wang; Chong Liu; Huan-Long Peng; Chao-Hong Shi; Kai-Zhi Xie; Kun Zhang; Li-Li Sun; Chang-Min Zhou; Wen-Jie Gu (Environmental Pollution, 2025)

Advanced micro-textural engineering for the fabrication of high-performance superomniphobic surfaces - Chang Lv; Tao Wang; Yuanwei Ding; Haiyan Li; Yulong Ying; Lvlv Ji; Weihao Cui; Lei Liu; Sheng Wang (Chemical Engineering Journal, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

α-Linolenic acid promotes testosterone synthesis by improving mitochondrial function in primary rooster Leydig cells - Xuerui Chang; Danyang Li; Yong Guo; Xihui Sheng; Xiangguo Wang; Kai Xing; Longfei Xiao; Xueze Lv; Cheng Long; Xiaolong Qi (Theriogenology, 2025)

7-Hydroxycoumarin and its conjugated metabolites interact with organic anion transporters 1 and 3 in vitro and in vivo - Lijun Luo; Yongchun Chang; Weilin Zhang; Xiao Liu; Junpu Ge; Jieyi Chen; Yan Li; Dan Zhang; Li Sheng (Chemico-Biological Interactions, 2025)

A monochrome pipelined HMI system for foodborne microorganisms testing - Jia-Yong Song; Ze-Sheng Qin; Chang-Wen Xue; Li-Feng Bian; Chen Yang (Computers and Electronics in Agriculture, 2024)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Further geochronological constraints on the Xiuyan impact crater in northeast China - Zeyang Zhu; Chang Huang; Jing Wu; Yawei Li; Zhihao Sun; Min Zhang; Bin Zhang; Sheng-Hua Li; Jiaqi Liu (Frontiers of Earth Science, 2024)

The cause of an extreme sea surface warming in the midlatitude western North Pacific during 2012 summer - Zhiyuan Li; Gangfeng Wu; Chang Xu; Jing Zhao; Mengqiao Wang; Jie Sheng; Yi Shen; Xiao-Hua Zhu (Frontiers in Marine Science, 2024)
This study investigated an extreme sea surface warming in the midlatitude western North Pacific (MLWNP) during the summer of 2012. The 2012 extreme event was characterized by warm sea surface temperature anomaly (SSTA) extending from the East/Japan Sea to central North Pacific. The SSTA box–averaged over the MLWNP (130–180°E, 33–50°N) in 2012 ranked as the third warmest in recent four decades, which has caused intense marine heatwaves in this region. During the summer of 2012, a positive Indian Ocean Dipole event co-occurred with El Niño, favoring anomalous moisture transport between the two basins that caused enhanced convection in the South China and Philippine Seas and western–to–central subtropical Pacific. The enhanced convective activities triggered two meridional atmospheric Rossby wave trains to form strong atmospheric blocking high–pressure systems in the MLWNP. This reduced the total cloud cover and surface wind speed, enhancing insolation and reducing the release of latent heat flux. In addition, the weakened wind strengthened the stratification and shoaled the mixed layer. As a result, the increased net heat flux into the ocean accompanied by a shallower mixed layer contributed to the upper ocean warming in the MLWNP. Meanwhile, the North Pacific was dominated by a negative phase of Pacific Decadal Oscillation (PDO), significantly contributing to warm SSTAs in the MLWNP in 2012. Consequently, the 2012 extreme warming in the MLWNP was the results of the combination of atmospheric Rossby waves and PDO. Our study highlighted the roles of high–frequency atmospheric teleconnection and low–frequency PDO in extreme sea surface warming in the MLWNP.

Elevated temperature affects the expression of signaling molecules in quail testes meiosis I prophase, but spermatogenesis remains normal - Qianwen Chang; Jiarong Li; Zihui Zhao; Qi Zhu; Yaning Zhang; Ruimin Sheng; Ziyin Yang; Mingcheng Dai; Pengchao Wang; Xiaorui Fan; Junping He (Theriogenology, 2024)

Flow characteristics of the rip current system adjacent to a coastal vertical structure for irregular waves - Jie Xu; Sheng Yan; Zhi-li Zou; Zhongbo Liu; Yan Wang; Cheng-shu Chang; Zhao-wei Wang; Zai-jin You (Ocean Engineering, 2024)

Improving the removal rate of bisphenol A and Cu2+ from water using P/N coexisting β-cyclodextrin-based adsorbents by enhancing adsorbents-pollutants interactions - Xiuqin Fang; Chang Wang; Hong-Hui Shu; Sheng-Li Han; Cheng-Mei Liu (Carbohydrate Polymers, 2024)

Alkaline-resistant covalent organic framework membranes for selective hydroxide ion separation - Yuan Xia; Daojiang Zhu; Chang Huang; Tingting Xu; Fangmeng Sheng; Xingya Li; Tongwen Xu (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Ultrahigh-response flexible photothermoelectric photodetectors based on a graded Bi2Te3-carbon nanotube hybrid - Chao Chen; Hai-Long Yu; Yi-Ming Zhao; Peng-Xiang Hou; Shu-Yu Guo; Sheng-Qian Li; Hao-Zike Wang; Kaiping Tai; Chang Liu (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Xanthohumol combined with chitosan-oxidized starch film as a potential new strategy for food packaging: Characterization, physicochemical and biological properties - Fan Yang; Siyuan Chang; Lin Zhao; Jing Han; Hao Li; Sen Zhang; Sheng Guo; Jinao Duan (Food Packaging and Shelf Life, 2024)

Remediation of petroleum-contaminated site soil by bioaugmentation with immobilized bacterial pellets stimulated by a controlled-release oxygen composite - Sheng Zhao; Ling-ling Li; Yue-jie Wang; Zheng-wei Liu; Shuai Yang; Xiang Gao; Chang-yun Zhang; An-feng Yu (Environmental Pollution, 2024)

Local microenvironment modulation of zirconium-porphyrinic frameworks for CO2 reduction - Xue Zhao; Chang-Yan Zhu; Heng Rao; Dong-Ying Du; Min Zhang; Ping She; Li Li; Jun-Sheng Qin (Chemical Engineering Journal, 2024)

Solution-processable organic–inorganic materials with colorful afterglow at room temperature - Sheng-Hua Li; Tuo-Yu Zhou; Shu-Yue Yang; Tai-Wen Li; Penglin Zhang; Guang-Yue Li; Chang Li; Hong-Qiao Li; Jing-Yi Li; Qian Zhao (Chemical Engineering Journal, 2024)

Polar bear hair inspired 3D photothermal evaporator for efficient solar steam desalination and electricity generation - Haiyan Li; Chang Lv; Cheng Qian; Haimei Liu; Tao Wang; Sheng Wang (Chemical Engineering Journal, 2024)

In vivo EPID-based daily treatment error identification for volumetric-modulated arc therapy in head and neck cancers with a hierarchical convolutional neural network: a feasibility study - Yiling Zeng; Heng Li; Yu Chang; Yang Han; Hongyuan Liu; Bo Pang; Jun Han; Bin Hu; Junping Cheng; Sheng Zhang; Kunyu Yang; Hong Quan; et al. (Physical and Engineering Sciences in Medicine, 2024)

Effect of a six-year Biochar Amendment on Water Productivity and Nitrogen Utilization of Maize and Comprehensive Soil Fertility - Xuanming Wang; Xu Su; Lixue Wang; Sheng Li; Minru Chang; Yanqi Li; Yu Guan; Qi Wu; Wenzhong Zhang (Journal of Soil Science and Plant Nutrition, 2024)

Dynamic Response of Roadbed Soil Under Various Dynamic Load Waveforms - Xin-Sheng Zhang; Yan-Ge Chen; Chang-Biao He; Zhen Li; Lei Liao; Yun Cheng; Yin-Lei Sun (Geotechnical and Geological Engineering, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Effects of Enterobacter cloacae insecticidal protein on the Duox-ROS system and midgut bacterial community and function of Galleria mellonella larvae - Tao Zhu; Yi Yang; Chao Hu; Liang Ma; Jiaqing Sheng; Ruiying Chang; Yanfei Liao; Lianzhe Wang; Yutao Zhu; Mei Zhao; Bingbing Li; Taotao Li; et al. (Toxicon, 2024)

Soil water consumption along the profile in response to soil water content variations in a black locust plantation with a rainfall exclusion in Loess Plateau - Mei-Jun Liu; Le Chang; Qiu-Wen Chen; Guoqing Li; Sheng Du (Journal of Hydrology, 2024)

Comprehensive reutilization of Glycyrrhiza uralensis residue by extrusion-biological pretreatment for coproduction of flavonoids, cellulase, and ethanol - Siyuan Chang; Chenke Yun; Bingqian Yang; Jinao Duan; Tianyi Chen; Lei Liu; Bingfeng Li; Sheng Guo; Sen Zhang (Bioresource Technology, 2024)

Spatial and Temporal Distribution Characteristics and Cytotoxicity of Atmospheric PM2.5 in the Main Urban Area of Lanzhou City - Jinyu Wang; Yanni Zheng; Qing Gao; Haodong Zhou; Xuhong Chang; Jinxia Gao; Sheng Li (Bulletin of Environmental Contamination and Toxicology, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

Learning-based double layer control method of yaw stability simulation research for rear wheel independent drive electric tractor plowing operation - Zhen-hao Luo; Bin Xie; Zhong-ju Chen; Sheng-li Zhang; Zi-hao Zhao; Bo-wen Zheng; Chang-kai Wen; Zheng-he Song (Computers and Electronics in Agriculture, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

The De underestimation caused by the unstable medium component in the initial OSL signal from lava-baked quartz and correction strategies - Chun-Xin Wang; Chang Huang; Anchuan Fan; Sheng-Hua Li (Quaternary Geochronology, 2024)

Fruit grading system by reconstructed 3D hyperspectral full-surface images - Jia-Yong Song; Ze-Sheng Qin; Chang-Wen Xue; Li-Feng Bian; Chen Yang (Postharvest Biology and Technology, 2024)

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Endophytic bacteria for Cd remediation in rice: Unraveling the Cd tolerance mechanisms of Cupriavidus metallidurans CML2 - Yuan Zhang; Qi Zhou; Chang Gao; Yue Lu; Yang Sheng; Ming Xiao; Yueli Yun; Jonathan Nimal Selvaraj; Xianhua Zhang; Yadong Li; Xuejing Yu (Journal of Hazardous Materials, 2024)

Biochar reduces gaseous emissions during poultry manure composting: Evidence from the evolution of associated functional genes - Ruijing Dang; Yu Cai; Jiaming Li; Yilin Kong; Tao Jiang; Jiali Chang; Sheng Yao; Jing Yuan; Guoxue Li; Guoying Wang (Journal of Cleaner Production, 2024)

Oxidative stress and potential effects of metal nanoparticles: A review of biocompatibility and toxicity concerns - Yung-Li Wang; Yu-Hsuan Lee; Chu-Lin Chou; Yu-Sheng Chang; Wen-Chih Liu; Hui-Wen Chiu (Environmental Pollution, 2024)

Designing hollow mesoporous carbon sphere for high-rate supercapacitor in water-in-salt electrolyte - Liping Feng; Huichao Liu; Wenyan Zan; Sidian Li; Yunzhen Chang; Ying Zhang; Wenjing Hou; Yun Zhao; Sheng Zhu; Gaoyi Han (Chemical Engineering Journal, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Improving monthly mean land surface temperature estimation by merging four products using the generalized three-cornered hat method and maximum likelihood estimation - Si-Bo Duan; Shuangquan Zhou; Zhao-Liang Li; Xiangyang Liu; Sheng Chang; Meng Liu; Cheng Huang; Xia Zhang; Guofei Shang (Remote Sensing of Environment, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Growth characteristics and biomass model of Cupressus gigantea sapling - Liu Chang-Sheng; Li Tao; Zhang Rui-wen; Wang Chao; Qu Xing-le; Luo Da-qing (Trees, 2024)

The remediation potential and kinetics of Pb2+ adsorbed by the organic frameworks of Cladophora rupestris - Lu-sheng Zhang; Xiao-yu Feng; Chang-fa Qiu; Ling-sheng Li; Yu Sun; Xin-yi Tao; Xin-yue Li; Zhao-wen Liu; De-ju Cao (Environmental Science and Pollution Research, 2024)

Analysis of the effect of multiple thermal-cold cycles on the bearing performance of phase change energy piles - Hong Chang; Sheng Jiang; Haozhi Jiang; Yunjie Li; Zhengheng Gan; Songying Zhao (Geothermics, 2024)

3D Printing windows and rheological properties for normal maize starch/sodium alginate composite gels - Ying Cui; Fan Yang; Chang-sheng Wang; Andreas Blennow; Changyong Li; Xingxun Liu (Food Hydrocolloids, 2024)

Electro-forward osmosis through a titanium-dioxide-modified membrane to enhance aquaculture wastewater recovery - Yi-Li Lin; Nai-Yun Zheng; Yu-Sheng Chen; Chao-Chin Chang (Desalination, 2024)

A flexible electrochromic device with variable infrared emissivity based on W18O49 nanowire cathode and MXene infrared transparent conducting electrode - Jing Zhao; Shengliang Zhang; Sheng Chang; Chong Li; Chang Fang; Xianjie Xia; Laifa Shen; Jim Yang Lee; Chen Cao; Xiaogang Zhang; Yimin Xuan (Chemical Engineering Journal, 2024)

Cyclophosphamide reduces gene transcriptional activity and embryo in vitro development by inhibiting NF-κB expression through decreasing AcH4K12 - Zhao-Bo Luo; Liu-Hui Yang; Sheng-Zhong Han; Shuang-Yan Chang; Hongye Liu; Zhi-Yong An; Xiu-Li Zhang; Biao-Hu Quan; Xi-Jun Yin; Jin-Dan Kang (Chemico-Biological Interactions, 2024)

Long-term grazing improved soil chemical properties and benefited community traits under climatic influence in an alpine typical steppe - Yu-Wen Zhang; Ze-Chen Peng; Sheng-Hua Chang; Zhao-Feng Wang; Duo-Cai Li; Yu-Feng An; Fu-Jiang Hou; Ji-Zhou Ren (Journal of Environmental Management, 2023)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Efficient C = O bond hydrogenation of cinnamaldehyde over PtCu alloy frame: Insight into the morphology and Pt species state - Yan Jiang; Qian Chang; Lifang Guan; Botao Teng; Congcong Xu; Yang Zhang; Xiang Li; Qiang Sheng; Yue Yao; Shuxiang Lu; Yuchen Qin (Chemical Engineering Journal, 2023)

Comparative study about ozonation to treat Microcystis-laden source water at the development and maintenance stage - Xi Li; XuanXuan Xian; Sheng Chen; Weijun Song; Xin Yu; Chang-Ping Yu (Chemosphere, 2023)

Dose-response formation of N7-(3-benzo[1,3]dioxol-5-yl-2-hydroxypropyl)guanine in liver and urine correlates with micronucleated reticulocyte frequencies in mice administered safrole oxide - Kuen-Yuh Wu; Yu-Tzu Wei; Yu-Syuan Luo; Li-Chin Shen; Bao-Suei Chang; Ya-Yin Chen; Yan-Chi Huang; Hui-Fen Huang; Wen-Sheng Chung; Su-Yin Chiang (Food and Chemical Toxicology, 2023)

Morphology-steered synthesis of Ce-MnO2 catalysts for catalytic oxidation of ethane at low temperature - Shasha Du; Jiangliang Hu; Jiancheng Wang; Sheng Wang; Jiancai Hou; Jiayu Li; Yudi Su; Liping Chang; Hongwei Qin; Yaqi Wang; Weiren Bao (Fuel, 2023)

Integrating ATAC-seq and RNA-seq to identify differentially expressed genes with chromatin-accessible changes during photosynthetic establishment in Populus leaves - Sheng-Ying Zhang; Biligen-Gaowa Zhao; Zhuo Shen; Ying-Chang Mei; Guo Li; Feng-Qin Dong; Jiao Zhang; Qing Chao; Bai-Chen Wang (Plant Molecular Biology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Activation of Cannabinoid Receptor 1 in GABAergic Neurons in the Rostral Anterior Insular Cortex Contributes to the Analgesia Following Common Peroneal Nerve Ligation - Ming Zhang; Cong Li; Qian Xue; Chang-Bo Lu; Huan Zhao; Fan-Cheng Meng; Ying Zhang; Sheng-Xi Wu; Yan Zhang; Hui Xu (Neuroscience Bulletin, 2023)
The rostral agranular insular cortex (RAIC) has been associated with pain modulation. Although the endogenous cannabinoid system (eCB) has been shown to regulate chronic pain, the roles of eCBs in the RAIC remain elusive under the neuropathic pain state. Neuropathic pain was induced in C57BL/6 mice by common peroneal nerve (CPN) ligation. The roles of the eCB were tested in the RAIC of ligated CPN C57BL/6J mice, glutamatergic, or GABAergic neuron cannabinoid receptor 1 (CB1R) knockdown mice with the whole-cell patch-clamp and pain behavioral methods. The E/I ratio (amplitude ratio between mEPSCs and mIPSCs) was significantly increased in layer V pyramidal neurons of the RAIC in CPN-ligated mice. Depolarization-induced suppression of inhibition but not depolarization-induced suppression of excitation in RAIC layer V pyramidal neurons were significantly increased in CPN-ligated mice. The analgesic effect of ACEA (a CB1R agonist) was alleviated along with bilateral dorsolateral funiculus lesions, with the administration of AM251 (a CB1R antagonist), and in CB1R knockdown mice in GABAergic neurons, but not glutamatergic neurons of the RAIC. Our results suggest that CB1R activation reinforces the function of the descending pain inhibitory pathway via reducing the inhibition of glutamatergic layer V neurons by GABAergic neurons in the RAIC to induce an analgesic effect in neuropathic pain.

Pirfenidone ameliorates liver steatosis by targeting the STAT3-SCD1 axis - Shan Yang; Renzi Zhang; Wenzhen Deng; Shichuan Chang; Yang Li; Sheng Li (Inflammation Research, 2023)

Magnetic three-phase single-drop microextraction for highly sensitive detection of aflatoxin B1 in agricultural product samples based on peroxidase-like spatial network structure - Jingyu Kuang; Jiahe Ju; Yongli Lu; Yitong Chen; Chang Liu; Dezhao Kong; Wei Shen; Hai-Wei Shi; Li Li; Jin Ye; Sheng Tang (Food Chemistry, 2023)

Prediction of Effector Proteins from Trichoderma longibrachiatum Through Transcriptome Sequencing - Jialin Zhang; Lijun Wang; Aizhi Ren; Yinsheng Sheng; Xue Chang; Xiaolong Li; Mengjiao Guan; Na Shang; Peibao Zhao; Shulei Sun (Current Microbiology, 2023)

Genetic variation reveals the enhanced microbial hyaluronan biosynthesis via atmospheric and room temperature plasma - Zhi-Yuan Yao; Jin-Song Gong; Yu-Ru Liu; Jia-Yu Jiang; Yue-Sheng Zhang; Chang Su; Heng Li; Chuan-Li Kang; Lei Liu; Zheng-Hong Xu; Jin-Song Shi (Carbohydrate Polymers, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Four new phenolic compounds from the fruits of Alpinia galanga - Pei Liu; Sheng-Li Wu; Tian Wang; Xue-Mei Zhang; Chang-An Geng (Phytochemistry Letters, 2023)

Synthesis of novel adsorbent S-SiO2@Fe3O4 based on strong bonding of S-O-Se for selenium removal in water - Chang-Xian Zhao; Xin-Peng Ma; Xue-Lei Duan; Qi Guo; Sheng-Li Niu; Wen-Jing Zhou; Yuan-Ming Cao; Chun-Gang Yuan (Journal of Environmental Chemical Engineering, 2023)

Electrocatalyst with fluorinated protective layer for efficient oxygen reduction in the operating temperature of PEMFCs - Chang Li; Wenlong Wang; Sheng Zhu; Hui Pan; Qunjie Xu; PengHui Shi; YuLin Min (Chemical Engineering Journal, 2023)

Understanding the shortboard of regional sustainable development: fairness and efficiency of rural public resource allocation in China - Sheng Zhang; Ge Li; Ran Yu; Yuanhua Chang; Yifu Yang; Qihao Zhang; Weining Liu; Jiming Hao (Environment, Development and Sustainability, 2023)

PFO5DoDA disrupts hepatic homeostasis primarily through glucocorticoid signaling inhibition - Chang Wang; Huayu Fu; Jun Yang; Lei Liu; Fenghong Zhang; Chunyu Yang; Hongyuan Li; Jiamiao Chen; Qi Li; Xiaolin Wang; Yaorui Ye; Nan Sheng; et al. (Journal of Hazardous Materials, 2023)

A linkage between early Silurian Nb-REE enriched alkaline magmatism and Neoproterozoic subduction metasomatized mantle in South Qinling, Central China - Jian-Hui Su; Xin-Fu Zhao; Xiao-Chun Li; Sheng-Ren Chang; Yuan-Bao Wu; Carl Spandler (Lithos, 2023)

Prediction of coalbed methane content based on seismic identification of key geological parameters: a case in a study area, Southern Qinshui Basin - Jing Liu; Suoliang Chang; Sheng Zhang; Yanrong Li; Yaju hao; Guoxian He; You He; Bo Liu (Acta Geophysica, 2023)

Benthic suspension-feeding clams affect sedimentary microbial communities and nitrogen cycling in seawater pond IMTA - Sheng-Yi Yuan; Wen-Jun Zhu; Amir Neori; Ying Zhang; Meng Li; Jian Li; Zhi-Qiang Chang (Aquaculture, 2023)

Amphiphilic ligand in situ assembly of uranyl active sites and selective interactions of molybdenum disulfide - Yuhui Liu; Yaning Lu; Shuang Zhang; Xiaoyan Li; Zhibin Zhang; Liya Ge; MengYu Chang; Yunhai Liu; Grzegorz Lisak; Sheng Deng (Journal of Hazardous Materials, 2023)

Activation of sulfite by FeS for anaerobic fermentation enhancement of waste activated sludge: Performance and mechanisms - Xianli Yang; Jingnan Yang; Xuran Liu; Sheng Gong; Xiaodi Ji; Jianmin Chang; Chenxi Li; Qinyi Pan; Dongbo Wang (Chemical Engineering Journal, 2023)

Facile synthesis of Fe3C-dominated Fe/Fe3C/FeN0.0324 multiphase nanocrystals embedded in nitrogen-modified graphitized carbon as efficient pH-universal catalyst for oxygen reduction reaction and zinc-air battery - Guang Li; Kuang Sheng; Yu Lei; Juan Yang; Yulian Chen; Xiaowei Guo; Gairong Chen; Baobao Chang; Tianjing Wu; Xianyou Wang (Chemical Engineering Journal, 2023)

Residues of polychlorinated biphenyls (PCBs) in a wild predatory fish from an e-waste site in South China between 2009 and 2016 - Chang-an Li; Si-sheng Li; Ying Zhang; Yichao Huang; Lin Tao (Environmental Science and Pollution Research, 2023)

AIoT-Based Ergometer for Physical Training in Frail Elderly with Cognitive Decline: A Pilot Randomized Control Trial - Chih-Chun Lin; Li-Chieh Kuo; Yu-Sheng Lin; Chia-Ming Chang; Fang Wen Hu; Yi-Jing Chen; Chun-Tse Lin; Fong-Chin Su (Journal of Medical and Biological Engineering, 2022)
Purpose Reduced physical activity is reported in the elderly, especially in institutional residents. Institutionalized older adults exhibit a high prevalence of frailty. In this work, we developed an artificial intelligence of things (AIoT)-based feedback assistive strengthening ergometer (AIFASE), for the physical strengthening of the elderly with intelligent assistance. Methods We conducted a 12-week intervention in a long-term care facility. In total, 16 participants (84.38 ± 6.0 years; 4 males and 12 females) were recruited with 1:1 randomization of exercise to control groups. The muscle strength of the lower extremities, timed up and go test (TUG), and Short-form Physical Performance Battery (SPPB) of the participants were measured. The AIFASE system allows the clinical staff to record the personal physical performance of the elderly and generates personalized exercise prescriptions accordingly. AIFASE also displays the current usage status of all ergometers and the users’ physiological conditions. The algorithms were developed to generate warning alerts when the training workload was too large by personal physiological detection. AIFASE automatically customized the exercise prescription according to the user’s exercise performance. Results After a 12-week AIFASE intervention, the intervention group exhibited significant improvements in the strength of the hip flexor, Semi-Tandem Stand, and Tandem Stand. Conclusion In this study, we developed an AIoT ergometer that delivered customized physical training prescriptions to improve the physical performance of long-term care facility residents. We believe that the application of AIFASE will help improve the quality of institutional care.

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Mycotoxin surveillance on wheats in Shandong province, China, reveals non-negligible probabilistic health risk of chronic gastrointestinal diseases posed by deoxynivalenol - Fenghua Li; Xinglan Duan; Liwen Zhang; Dafeng Jiang; Xianqi Zhao; En Meng; Ran Yi; Chang Liu; Yirui Li; Jia-Sheng Wang; Xiulan Zhao; Wei Li; et al. (Environmental Science and Pollution Research, 2022)

CRIF1 promotes the progression of non-small-cell lung cancer by SIRT3- mediated deacetylation of PYCR1 - Qi Wang; Zhuolin Xie; Chang Li; Chun Xu; Cheng Ding; Sheng Ju; Jun Chen; Zihan Cui; Chen Chen; Biao Gu; Tengteng Wei; Jun Zhao (Journal of Molecular Histology, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Romidepsin (FK228) improves the survival of allogeneic skin grafts through downregulating the production of donor-specific antibody via suppressing the IRE1α-XBP1 pathway - Yuliang Guo; Siyu Song; Xiaoxiao Du; Li Tian; Man Zhang; Hongmin Zhou; Zhonghua Klaus Chen; Sheng Chang (Journal of Zhejiang University-SCIENCE B, 2022)

Trichocladabiflavone A, a chalcone-flavonone type biflavonoid from Selaginella trichoclada Alsto - Yang Xie; Xiao-Chang Yao; Lei-Hong Tan; Hong-Ping Long; Ping-Sheng Xu; Jing Li; Gui-Shan Tan (Natural Product Research, 2022)

Integrated seismic–geological prediction of tectonic coal via main controlling factors - Jing Liu; Suoliang Chang; Sheng Zhang; Yanrong Li; Qiang Chen (Acta Geophysica, 2022)

Increasing nitrogen supply to phosphorus-deficient Medicago sativa decreases shoot growth and enhances root exudation of tartrate to discharge surplus carbon dependent on nitrogen form - Honghua He; Zekun Zhang; Qi Peng; Chao Chang; Rui Su; Xiao Cheng; Yingxin Li; Jiayin Pang; Sheng Du; Hans Lambers (Plant and Soil, 2021)

Methyl jasmonate elicits distinctive hydrolyzable tannin, flavonoid, and phyto-oxylipin responses in pomegranate (Punica granatum L.) leaves - Lijing Chang; Sheng Wu; Li Tian (Planta, 2021)
Main conclusion Transcriptome and biochemical analyses suggested that, while suppression of multiple flavonoids and anthocyanins occurs at least partially at the transcriptional level, increased biosynthesis of non-jasmonate phyto-oxylipins is likely controlled non-transcriptionally. Abstract Methyl jasmonate (MeJA) produced in plants can mediate their response to environmental stresses. Exogenous application of MeJA has also shown to activate signaling pathways and induce phytoalexin accumulation in many plant species. To understand how pomegranate plants respond biochemically to environmental stresses, metabolite analysis was conducted in pomegranate leaves subjected to MeJA application and revealed unique changes in hydrolyzable tannins, flavonoids, and phyto-oxylipins. Additionally, transcriptome and real-time qPCR analyses of mock- and MeJA-treated pomegranate leaves identified differentially expressed metabolic genes and transcription factors that are potentially involved in the control of hydrolyzable tannin, flavonoid, and phyto-oxylipin pathways. Molecular, biochemical, and bioinformatic characterization of the only lipoxygenase with sustained, MeJA-induced expression showed that it is capable of oxidizing polyunsaturated fatty acids, though not located in the subcellular compartment where non-jasmonate (non-JA) phyto-oxylipins were produced. These results collectively suggested that while the broad suppression of flavonoids and anthocyanins is at least partially controlled at the transcriptional level, the induced biosynthesis of non-JA phyto-oxylipins is likely not regulated transcriptionally. Overall, a better understanding of how pomegranate leaves respond to environmental stresses will not only promote plant health and productivity, but also have an impact on human health as fruits produced by pomegranate plants are a rich source of nutritional compounds.

Bioaccumulation and translocation of trace elements in soil-irrigation water-wheat in arid agricultural areas of Xin Jiang, China - Muyesaier Tudi; Huada Daniel Ruan; Yunjiang Yu; Li Wang; Binggan Wei; Shuangmei Tong; Chang Kong; Lin-sheng Yang (Ecotoxicology, 2021)

A Survey on How Ocular Surface Demodex Infestation Interactively Associates with Diabetes Mellitus and Dry Eye Disease - Chang Huang; Shuze Chen; Sheng Fu; Yingli Li; Zhenhao Li; Siqi Li; Xiaoqian Liang; Zihong Wang; Zhoucheng Wang; Yifan Chen; Qixin Deng; Guoguo Yi; et al. (Acta Parasitologica, 2021)
Purpose Prevention of ocular surface (OS) Demodex infestation plays an important role in OS hygiene and variety of factors may be associated with it, in which diabetes mellitus (DM) or dry eye disease (DED) has caught the attention of most scholars. However, there has been no research on whether there was a potential interaction between DM and DED in the process of OS Demodex infestation. This cross-sectional study was implemented in Zhujiang Hospital of Southern Medical University. Methods Ophthalmologic interviews, questionnaires, and examinations were conducted. Factors including general information, DM status, dry eye condition, etc. were collected to study the correlation of DM and DED on OS Demodex infestation. Results After statistical analysis, we found that both DM ( P P = 0.013 R = 0.197, P R = 0.299, P P Conclusion This study provides a new evidence-based basis for clinical prevention and management of OS Demodex infestation.

Estimation of mountain block recharge on the northern Tianshan Mountains using numerical modeling - Jian-hua Ping; Ya-qiang Zhu; Xue-mei Mei; Wei Leng; Sheng Li; Ji-chang Zhao (Journal of Mountain Science, 2021)

Molecular Imaging for Radiolabeling a PSMA-Targeted Long Circulating Peptide as a Theranostic Agent in Mice Bearing a Human Prostate Tumor - Ming-Hsin Li; Sheng-Nan Lo; Ming-Wei Chen; Wei-Lin Lo; Yuan-Ruei Huang; Shih-Ying Lee; Su-Jung Chen; Shih-Wei Lo; Shih-Ming Wang; Chih-Hsien Chang (Journal of Medical and Biological Engineering, 2021)

Mechanism of colluvial landslide induction by rainfall and slope construction: A case study - Zhou Zhou; Jun-hui Shen; Ying Li; Wei-feng Duan; Ri-chang Yang; Jun-cheng Shu; He-wei Li; Sheng-yu Tao; Sheng-zhe Zheng (Journal of Mountain Science, 2021)

Ecological and health risk assessment of trace elements in surface soil in an arid region of Xin Jiang, China - Muyesaier Tudi; Huada Daniel Ruan; Binggan Wei; Li Wang; Shuangmei Tong; Chang Kong; Lin-sheng Yang (Journal of Soils and Sediments, 2021)

Isoorientin exerts a urate-lowering effect through inhibition of xanthine oxidase and regulation of the TLR4-NLRP3 inflammasome signaling pathway - Meng-Fei An; Ming-Yue Wang; Chang Shen; Ze-Rui Sun; Yun-Li Zhao; Xuan-Jun Wang; Jun Sheng (Journal of Natural Medicines, 2021)

Artificial Neural Network-based prediction of glacial debris flows in the ParlungZangbo Basin, southeastern Tibetan Plateau, China - Wang Tang; Hai-tao Ding; Ning-sheng Chen; Shang-Chang Ma; Li-hong Liu; Kang-lin Wu; Shu-feng Tian (Journal of Mountain Science, 2021)

Relationships among cigarette smoking, urinary biomarkers, and urothelial carcinoma risk: a case-control study - Chi-Jung Chung; Hui-Tsung Hsu; Chao-Hsiang Chang; Sheng-Wei Li; Chiu-Shong Liu; Mu-Chi Chung; Guo-Wei Wu; Wei-Ting Jung; Yen-Jung Kuo; Hui-Ling Lee (Environmental Science and Pollution Research, 2020)

Using sowing date management to promote micronutrient quality and alleviate cadmium accumulation in rice grains - Lin-lin Shi; Ming-xing Shen; Hong-jun Wu; Chang-ying Lu; Li-juan Mei; Xin-lian Zhu; Hai-hou Wang; Yun-Sheng Song (Cereal Research Communications, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Intestinal Polyp Recognition Based on Salient Codebook Locality-Constrained Linear Coding with Annular Spatial Pyramid Matching - Dongwei He; Sheng Li; Xiongxiong He; Liping Chang; Ni Zhang; Qianru Jiang (Journal of Medical and Biological Engineering, 2020)

Experimental investigation for dynamic instability of coal-rock masses in horizontal section mining of steeply inclined coal seams - Zheng-yi Wang; Lin-ming Dou; Jiang He; An-ye Cao; Xiong-wei Li; Peng-bo Li; Chang-sheng Wu (Arabian Journal of Geosciences, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

Crosstalk between PKC and MAPK pathway activation in cardiac fibroblasts in a rat model of atrial fibrillation - Wei-hua Guo; Xian Wang; Mei-sheng Shang; Zhe Chen; Qi Guo; Li Li; Hai-ying Wang; Rong-hui Yu; Chang-sheng Ma (Biotechnology Letters, 2020)

Perfusion Changes of Unexplained Early Neurological Deterioration After Reperfusion Therapy - Jingjing Fu; Ying Zhou; Qingqing Li; Genlong Zhong; Sheng Zhang; Ruiting Zhang; Chang Liu; Minming Zhang; Min Lou (Translational Stroke Research, 2020)

AAV/BBB-Mediated Gene Transfer of CHIP Attenuates Brain Injury Following Experimental Intracerebral Hemorrhage - Shuo Zhang; Zheng-wei Hu; Hai-yang Luo; Cheng-yuan Mao; Mi-bo Tang; Yu-sheng Li; Bo Song; Yao-he Wang; Zhong-xian Zhang; Qi-meng Zhang; Li-yuan Fan; Yao Zhang; et al. (Translational Stroke Research, 2020)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

Contrasting soil fungal communities at different habitats in a revegetated copper mine wasteland - Jie-liang Liang; Jun Liu; Tao-tao Yang; Pan-deng Wang; Sheng-chang Zhang; Pu Jia; Bin Liao; Wen-sheng Shu; Jin-tian Li (Soil Ecology Letters, 2020)

Remote Sensing for Detecting Changes of Land Use in Taipei City, Taiwan - Li Chen; Hsiao-Yu Wang; Tai-Sheng Wang; Chang-Huan Kou (Journal of the Indian Society of Remote Sensing, 2019)

Water Requirement for Irrigation of Complicated Agricultural Land by Using Classified Airborne Digital Sensor Images - Li Chen; Ta-Wei Chien; Chia-Sheng Hsu; Chih-Hung Tan; Hsiang-Yi Hsu; Chang-Huan Kou (Journal of the Indian Society of Remote Sensing, 2019)

Environment‐ and trait‐mediated scaling of tree occupancy in forests worldwide - Haibao Ren; Petr Keil; Xiangcheng Mi; Keping Ma; Zhanqing Hao; Wanhui Ye; Luxiang Lin; Renato Valencia; Christine Dawn Fletcher; Duncan W. Thomas; Robert W. Howe; James Lutz; et al. (Global Ecology and Biogeography, 2019)
Aim The relationship between the proportion of sites occupied by a species and the area of a site [occupancy–area relationship (OAR)] offers key information for biodiversity management and has long fascinated ecologists. We quantified the variation in OAR for 3,157 woody species in 17 forest plots worldwide and tested the relative importance of environment and species traits for explaining this variation and evaluated overall model predictive ability. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We used mixed‐effect regression to examine the observed shape of the OAR (its “slope”) against species‐specific and plot‐wide predictors: coarse‐grain occupancy, tree size, plot species richness, energy availability and topographic complexity. Results We found large variation in OAR slopes, and the variation was strongest among species within plots. The OAR slopes showed a latitudinal trend and were steeper near the equator. As predicted, coarse‐grain occupancy and tree size negatively affected OAR slopes, whereas species richness had a positive effect and explained most of the variance between plots. Although hypothesized directionalities were broadly confirmed, traits and environment had relatively limited overall predictive power. Main conclusions These results document the variation of the OAR for 3,157 species at near‐global extent. We found a latitudinal gradient in OAR slopes and confirmed key hypothesized predictors. But at this global extent and over the large set of species analysed, the remaining unexplained variation in OAR slopes was substantial. Nevertheless, this large‐scale empirical analysis of the OAR offers an initial step towards a more general use of OARs for the fine‐scale prediction of species distributions and abundance.

Calpain-2 promotes MKP-1 expression protecting cardiomyocytes in both in vitro and in vivo mouse models of doxorubicin-induced cardiotoxicity - Dong Zheng; Zhaoliang Su; Yi Zhang; Rui Ni; Guo-Chang Fan; Jeffrey Robbins; Long-Sheng Song; Jianmin Li; Tianqing Peng (Archives of Toxicology, 2019)

Multiparasitism with Trichogramma dendrolimi on egg of Chinese oak silkworm, Antheraea pernyi, enhances emergence of Trichogramma ostriniae - Tian-Hao Li; Chun-Yu Tian; Lian-Sheng Zang; Yang-Yang Hou; Chang-Chun Ruan; Xiangbing Yang; Lucie Monticelli; Nicolas Desneux (Journal of Pest Science, 2019)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Transcriptome analysis of wheat seedling and spike tissues in the hybrid Jingmai 8 uncovered genes involved in heterosis - Yong-jie Liu; Shi-qing Gao; Yi-miao Tang; Jie Gong; Xiao Zhang; Yong-bo Wang; Li-ping Zhang; Ren-wei Sun; Quan Zhang; Zhao-bo Chen; Xiang Wang; Cai-juan Guo; et al. (Planta, 2018)

Erratum to: Hypoxia Augments Increased HIF-1a and Reduced Survival Protein p-Akt in Gelsolin (GSN)-Dependent Cardiomyoblast Cell Apoptosis - Yu-Lan Yeh; Wei-Syun Hu; Wei-Jen Ting; Chia-Yao Shen; Hsi-Hsien Hsu; Li-Chin Chung; Chuan-Chou Tu; Sheng-Huang Chang; Cecilia-Hsuan Day; Yuhsin Tsai; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2018)

Three-dimensional analysis of ozone and PM2.5 distributions obtained by observations of tethered balloon and unmanned aerial vehicle in Shanghai, China - Xiao-Bing Li; Dongfang Wang; Qing-Chang Lu; Zhong-Ren Peng; Qingyan Fu; Xiao-Ming Hu; Juntao Huo; Guangli Xiu; Bai Li; Chao Li; Dong-Sheng Wang; Hanyu Wang (Stochastic Environmental Research and Risk Assessment, 2018)

The key gluconeogenic gene PCK1 is crucial for virulence of Botrytis cinerea via initiating its conidial germination and host penetration - Jian‐Kang Liu; Hao‐Wu Chang; Yue Liu; Yu (Haity) Qin; Yu‐Han Ding; Lan Wang; Yue Zhao; Ming‐Zhe Zhang; Sheng‐Nan Cao; Le‐Tao Li; Wei Liu; Gui‐Hua Li; et al. (Environmental Microbiology, 2018)
Summary The process of initiation of host invasion and survival of some foliar phytopathogenic fungi in the absence of external nutrients on host leaf surfaces remains obscure. Here, we demonstrate that gluconeogenesis plays an important role in the process and nutrient‐starvation adaptation before the pathogen host invasion. Deletion of phosphoenolpyruvate c arboxy k inase gene BcPCK1 in gluconeogenesis in Botrytis cinerea , the causative agent of grey mould, resulted in the failure of the Δ Bcpck1 mutant conidia to germinate on hard and hydrophobic surface and penetrate host cells in the absence of glucose, reduction in conidiation and slow conidium germination in a nutrient‐rich medium. The wild‐type and Δ Bcpck1 conidia germinate similarly in the presence of glucose (higher concentration) as the sole carbon source. Conidial glucose‐content should reach a threshold level to initiate germination and host penetration. Infection structure formation by the mutants displayed a glucose‐dependent fashion, which corresponded to the mutant virulence reduction. Exogenous glucose or complementation of BcPCK1 completely rescued all the developmental and virulence defects of the mutants. Our findings demonstrate that BcPCK1 plays a crucial role in B. cinerea pathogenic growth and virulence, and provide new insights into gluconeogenesis mediating pathogenesis of plant fungal pathogens via initiation of conidial germination and host penetration.

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Mapping and comparative proteomic analysis of the starch biosynthetic pathway in rice by 2D PAGE/MS - Tao-Shan Chang; Chih-Wei Liu; Yu-Ling Lin; Chao-Yi Li; Arthur Z. Wang; Min-Wei Chien; Chang-Sheng Wang; Chien-Chen Lai (Plant Molecular Biology, 2017)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

Predicting Sea Surface Salinity Using an Improved Genetic Algorithm Combining Operation Tree Method - Li Chen; Basmah Alabbadi; Chih-Hung Tan; Tai-Sheng Wang; Kuo-Chang Li (Journal of the Indian Society of Remote Sensing, 2017)

Molecular and immune response characterizations of a novel Bax inhibitor-1 gene in pufferfish, Takifugu obscurus - Chang-Hong Cheng; Sheng-Wei Luo; An-Li Wang; Zhi-Xun Guo (Fish Physiology and Biochemistry, 2017)

Association of GWAS-Reported Variant rs11196288 near HABP2 with Ischemic Stroke in Chinese Han Population - Shao-hua Li; Chang-he Shi; Yu-sheng Li; Fang Li; Mi-bo Tang; Xin-jing Liu; Shuo Zhang; Zhi-lei Wang; Bo Song; Yu-ming Xu (Journal of Molecular Neuroscience, 2017)

Detection of chlorophylls in spores of seven ferns - Mei-Hwei Tseng; Kuei-Huei Lin; Yi-Jia Huang; Ya-Lan Chang; Sheng-Cih Huang; Li-Yaung Kuo; Yao-Moan Huang (Journal of Plant Research, 2017)

Screening somatic cell nuclear transfer parameters for generation of transgenic cloned cattle with intragenomic integration of additional gene copies that encode bovine adipocyte-type fatty acid-binding protein (A-FABP) - Yong Guo; Hejuan Li; Ying Wang; Xingrong Yan; Xihui Sheng; Di Chang; Xiaolong Qi; Xiangguo Wang; Yunhai Liu; Junya Li; Hemin Ni (Molecular Biology Reports, 2017)

Effects of saline water irrigation and fertilization regimes on soil microbial metabolic activity - Li -Juan Chen; Qi Feng; Yong-Ping Wei; Chang-Sheng Li; Yan Zhao; Hui-Ya Li; Bao-Gui Zhang (Journal of Soils and Sediments, 2017)

miRNA Expression Change in Dorsal Root Ganglia After Peripheral Nerve Injury - Hsueh-Ling Chang; Hung-Chen Wang; Yi-Ta Chunag; Chao-Wen Chou; I-Ling Lin; Chung-Sheng Lai; Lin-Li Chang; Kuang-I Cheng (Journal of Molecular Neuroscience, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Unsupervised segmentation of lung fields in chest radiographs using multiresolution fractal feature vector and deformable models - Wen-Li Lee; Koyin Chang; Kai-Sheng Hsieh (Medical & Biological Engineering & Computing, 2016)

Hypoxia Augments Increased HIF-1α and Reduced Survival Protein p-Akt in Gelsolin (GSN)-Dependent Cardiomyoblast Cell Apoptosis - Yu-Lan Yeh; Wei-Jen Ting; Chia-Yao Shen; Hsi-Hsien Hsu; Li-Chin Chung; Chuan-Chou Tu; Sheng-Huang Chang; Cecilia-Hsuan Day; Yuhsin Tsai; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2016)

A residue substitution in the plastid ribosomal protein L12/AL1 produces defective plastid ribosome and causes early seedling lethality in rice - Dong-sheng Zhao; Chang-quan Zhang; Qian-feng Li; Qing-qing Yang; Ming-hong Gu; Qiao-quan Liu (Plant Molecular Biology, 2016)

Spatial Variations of Soil Microbial Activities in Saline Groundwater-Irrigated Soil Ecosystem - Li-Juan Chen; Qi Feng; Chang-Sheng Li; You-Xi Song; Wei Liu; Jian-Hua Si; Bao-Gui Zhang (Environmental Management, 2016)

The impact of nitrogen amendment and crop growth on dissolved organic carbon in soil solution - Xiao-guo Wang; Chang-sheng Li; Yong Luo; Ke-ke Hua; Ming-hua Zhou (Journal of Mountain Science, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Genome-wide analysis of AP2/ERF transcription factors in carrot (Daucus carota L.) reveals evolution and expression profiles under abiotic stress - Meng-Yao Li; Zhi-Sheng Xu; Ying Huang; Chang Tian; Feng Wang; Ai-Sheng Xiong (Molecular Genetics and Genomics, 2015)

Screening for simple sequence repeat markers in Puccinia striiformis tritici based on genomic sequence - Gang-ming Zhan; Fu-ping Wang; Huai-yong Luo; Shu-chang Jiang; Wen-ming Zheng; Li-li Huang; Zhen-sheng Kang (Journal of Zhejiang University-SCIENCE B, 2015)

Molecular cloning and expression of a nitrite reductase gene from mulberry (Morus L.) - Xi-ling Wang; Ya-sheng Yu; Yan Yang; Chang-ying Liu; Jun Li; Mao-de Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Partial Volume Correction for Equivocal Retropharyngeal Nodal Metastases of Nasopharyngeal Carcinoma with Fluorodeoxyglucose Positron Emission Tomography–Computed Tomography - Yu-Wen Wang; Chin-Shun Wu; Chih-Han Chang; Kuo-Sheng Cheng; Yu-Kang Chang; I-Wen Huang; Chin-Li Lu; Wei-Jen Yao (Journal of Medical and Biological Engineering, 2015)

Impact of LPS-Induced Cardiomyoblast Cell Apoptosis Inhibited by Earthworm Extracts - Ping-Chun Li; Yun-Chen Tien; Cecilia Hsuan Day; Peiying Pai; Wei-Wen Kuo; Tung-Sheng Chen; Chia-Hua Kuo; Chang-Hai Tsai; Da-Tong Ju; Chih-Yang Huang (Cardiovascular Toxicology, 2015)

Rhodococcus soli sp. nov., an actinobacterium isolated from soil using a resuscitative technique - Shan-Hui Li; Xiao-Yun Yu; Dong-Jin Park; Wael N. Hozzein; Chang-Jin Kim; Wen-Sheng Shu; Mohammed A. M. Wadaan; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Isocitrate lyase is required for urediniospore germination of Puccinia striiformis f. sp. tritici - Jie Liu; Qiu-Ling Wang; Qing Chang; Li-Na Han; Guo-Liang Pei; Yue-Qing Xue; Lu-Meng Jia; Kun Zhang; Yuan-Yuan Duan; Zhen-Sheng Kang (Molecular Biology Reports, 2014)

Anti-apoptosis effect of polysaccharide isolated from the seeds of Cuscuta chinensis Lam on cardiomyocytes in aging rats - Shou-Li Sun; Li Guo; Ya-Chao Ren; Bing Wang; Rong-Hui Li; Yu-Shan Qi; Hui Yu; Nai-Dan Chang; Ming-Hui Li; Hai-Sheng Peng (Molecular Biology Reports, 2014)

Characteristics of Malignant Tumors in 230 Husband–Wife Pairs - Ju Liu; Zhijian Xu; Kai Zhang; Huai Li; Sheng Chang; Xiaofeng Bi; Min Dai (Cell Biochemistry and Biophysics, 2014)

Urinary metabolites of di(2-ethylhexyl) phthalate relation to sperm motility, reactive oxygen species generation, and apoptosis in polyvinyl chloride workers - Li-Ping Huang; Ching-Chang Lee; Jer-Pei Fan; Po-Hsiu Kuo; Tung-Sheng Shih; Ping-Chi Hsu (International Archives of Occupational and Environmental Health, 2014)

Gordonia jinhuaensis sp. nov., a novel actinobacterium, isolated from a VBNC (viable but non-culturable) state in pharmaceutical wastewater - Shan-Hui Li; Yi Jin; Juan Cheng; Dong-Jin Park; Chang-Jin Kim; Wael N. Hozzein; Mohammed A. M. Wadaan; Wen-Sheng Shu; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Gelsolin (GSN) induces cardiomyocyte hypertrophy and BNP expression via p38 signaling and GATA-4 transcriptional factor activation - Wei-Syun Hu; Tsung-Jung Ho; Peiying Pai; Li-Chin Chung; Chia-Hua Kuo; Sheng-Huang Chang; Fuu-Jen Tsai; Chang-Hai Tsai; Yu-Chi Jie; Ying-Ming Liou; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2014)

Silencing heat shock protein 27 (HSP27) inhibits the proliferation and migration of vascular smooth muscle cells in vitro - Jie Huang; Liang-di Xie; Li Luo; Su-li Zheng; Hua-jun Wang; Chang-sheng Xu (Molecular and Cellular Biochemistry, 2014)

EGF Enhances ADSCs Secretion via ERK and JNK Pathways - Qiang Li; Pei-hua Li; Dian-ju Hou; Ai-jun Zhang; Chang-bo Tao; Xue-yang Li; Pei-sheng Jin (Cell Biochemistry and Biophysics, 2014)

Cloning and molecular characterization of a myosin light chain gene from Puccinia striiformis f. sp. tritici - Jie Liu; Li-Na Han; Qiong Zhang; Qiu-Ling Wang; Qing Chang; Hua Zhuang; Jia Liu; Man Li; Dan Yu; Zhen-Sheng Kang (World Journal of Microbiology and Biotechnology, 2014)

MicroRNA-29a protects against acute liver injury in a mouse model of obstructive jaundice via inhibition of the extrinsic apoptosis pathway - Mao-Meng Tiao; Feng-Sheng Wang; Li-Tung Huang; Jiin-Haur Chuang; Ho-Chang Kuo; Ya-Ling Yang; Ying-Hsien Huang (Apoptosis, 2014)

Influence of Electromagnetic Signal of Antibiotics Excited by Low-Frequency Pulsed Electromagnetic Fields on Growth of Escherichia coli - Yin-Lung Ke; Fu-Yu Chang; Ming-Kun Chen; Shun-Lai Li; Ling-Sheng Jang (Cell Biochemistry and Biophysics, 2013)

Responses to booster hepatitis B vaccination are significantly correlated with genotypes of human leukocyte antigen (HLA)-DPB1 in neonatally vaccinated adolescents - Tzu-Wei Wu; Chen-Chung Chu; Tzu-Ying Ho; Huei-Wen Chang Liao; Sheng-Kai Lin; Marie Lin; Hans Hsienhong Lin; Li-Yu Wang (Human Genetics, 2013)

Hydro-mechanical coupling experiments on suffusion in sandy gravel foundations containing a partially penetrating cut-off wall - Yu-long Luo; Qiang Wu; Mei-li Zhan; Jin-chang Sheng; Yuan Wang (Natural Hazards, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

Construction of an SSH Library of Pinellia ternata Under Heat Stress, and Expression Analysis of Four Transcripts - Hedong Lu; Tao Xue; Aimin Zhang; Wei Sheng; Yanfang Zhu; Li Chang; Yunxian Song; Jianping Xue (Plant Molecular Biology Reporter, 2013)

Hydro-mechanical experiments on suffusion under long-term large hydraulic heads - Yu-long Luo; Liang Qiao; Xing-xing Liu; Mei-li Zhan; Jin-chang Sheng (Natural Hazards, 2013)

Comparison of MODIS land surface temperature and ground-based observed air temperature in complex topography - Yen-Jen Lai; Ching-Feng Li; Po-Hsiung Lin; Tsong-Hue Wey; Cheng-Sheng Chang (International Journal of Remote Sensing, 2012)

Characterization and Expression of a Phytochelatin Synthase Gene in Birch-leaf Pear (Pyrus betulaefolia Bunge) - You Hong Chang; Hui Li; Yu Cong; Jing Lin; Bao Long Sheng (Plant Molecular Biology Reporter, 2012)

Performance of four Chinese Trichogramma species as biocontrol agents of the rice striped stem borer, Chilo suppressalis, under various temperature and humidity regimes - Xiao-Hua Yuan; Li-Wei Song; Jun-Jie Zhang; Lian-Sheng Zang; Li Zhu; Chang-Chun Ruan; Guang-Zhi Sun (Journal of Pest Science, 2012)

The variation of tree beta diversity across a global network of forest plots - Miquel De Cáceres; Pierre Legendre; Renato Valencia; Min Cao; Li‐Wan Chang; George Chuyong; Richard Condit; Zhanqing Hao; Chang‐Fu Hsieh; Stephen Hubbell; David Kenfack; Keping Ma; et al. (Global Ecology and Biogeography, 2012)
Aims With the aim of understanding why some of the world's forests exhibit higher tree beta diversity values than others, we asked: (1) what is the contribution of environmentally related variation versus pure spatial and local stochastic variation to tree beta diversity assessed at the forest plot scale; (2) at what resolution are these beta‐diversity components more apparent; and (3) what determines the variation in tree beta diversity observed across regions/continents? Location World‐wide. Methods We compiled an unprecedented data set of 10 large‐scale stem‐mapping forest plots differing in latitude, tree species richness and topographic variability. We assessed the tree beta diversity found within each forest plot separately. The non‐directional variation in tree species composition among cells of the plot was our measure of beta diversity. We compared the beta diversity of each plot with the value expected under a null model. We also apportioned the beta diversity into four components: pure topographic, spatially structured topographic, pure spatial and unexplained. We used linear mixed models to interpret the variation of beta diversity values across the plots. Results Total tree beta diversity within a forest plot decreased with increasing cell size, and increased with tree species richness and the amount of topographic variability of the plot. The topography‐related component of beta diversity was correlated with the amount of topographic variability but was unrelated to its species richness. The unexplained variation was correlated with the beta diversity expected under the null model and with species richness. Main conclusions Because different components of beta diversity have different determinants, comparisons of tree beta diversity across regions should quantify not only overall variation in species composition but also its components. Global‐scale patterns in tree beta diversity are largely coupled with changes in gamma richness due to the relationship between the latter and the variation generated by local stochastic assembly processes.

Pseudonocardia nantongensis sp. nov., a novel endophytic actinomycete isolated from the coastal halophyte Tamarix chinensis Lour - Ke Xing; Sheng Qin; Guang-Kai Bian; Yue-Ji Zhang; Wen-Di Zhang; Chuan-Chao Dai; Chang-Hong Liu; Wen-Jun Li; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2012)

Landslides and catchment sedimentation in the Ta-Chia River influenced by the 1999 Taiwan Chi-Chi earthquake - Keh-Jian Shou; Li-Yuan Fei; Jiin-Fa Lee; Cheng-Yueh Wei; Sheng-Tsi Huang; You-Chang Lin (International Journal of Remote Sensing, 2012)

Passive stretch reduces calpain activity through nitric oxide pathway in unloaded soleus muscles - Peng-Tao Xu; Quan Li; Juan–Juan Sheng; Hui Chang; Zhen Song; Zhi-Bin Yu (Molecular and Cellular Biochemistry, 2012)

Pretreatment with anti-flagellin serum delays acute lung injury in rats with sepsis - Ming-Dong Hu; Yu Yang; Chang-Xi Zhou; Qi Li; Wang Yi; Gui-Sheng Qian; Mei Mao; Jian-Cheng Xu (Inflammation Research, 2012)

Streptomyces oceani sp. nov., a new obligate marine actinomycete isolated from a deep-sea sample of seep authigenic carbonate nodule in South China Sea - Xin-Peng Tian; Ying Xu; Jing Zhang; Jie Li; Zhong Chen; Chang-Jin Kim; Wen-Jun Li; Chang-Sheng Zhang; Si Zhang (Antonie van Leeuwenhoek, 2012)

A ground spectral model for estimating biomass at the peak of the growing season in Hulunbeier grassland, Inner Mongolia, China - Ji-Xi Gao; Yan-Mei Chen; Shi-Hai Lü; Chao-Yang Feng; Xue-Li Chang; Sheng-Xing Ye; Ji-Dong Liu (International Journal of Remote Sensing, 2012)

Celecoxib inhibits growth of human autosomal dominant polycystic kidney cyst-lining epithelial cells through the VEGF/Raf/MAPK/ERK signaling pathway - Tao Xu; Nian-Song Wang; Li-Li Fu; Chao-Yang Ye; Sheng-Qiang Yu; Chang-Lin Mei (Molecular Biology Reports, 2012)

Cloning and characterization of the actin gene from Puccinia striiformis f. sp. tritici - Jie Liu; Qiong Zhang; Qing Chang; Hua Zhuang; Li-Li Huang; Zhen-Sheng Kang (World Journal of Microbiology and Biotechnology, 2012)

TNF-α Increases Bone Marrow Mesenchymal Stem Cell Migration to Ischemic Tissues - Qiong Xiao; Shi-kun Wang; Hua Tian; Li Xin; Zhi-geng Zou; Yan-lai Hu; Cui-ming Chang; Xue-ying Wang; Qun-sheng Yin; Xiang-hong Zhang; Li-yan Wang (Cell Biochemistry and Biophysics, 2012)

Polymorphisms in chicken extracellular fatty acid binding protein gene - Zhi-yuan Zhao; Li Zhang; Bing-wang Du; Ning-xian Cao; Xin-sheng Jiang; Wen-xia Tian; Shu-jun Li; Wei-wei Wu; Chang-hui Ye (Molecular Biology Reports, 2012)

Begomovirus–whitefly mutualism is achieved through repression of plant defences by a virus pathogenicity factor - TONG ZHANG; JUN‐BO LUAN; JIN‐FENG QI; CHANG‐JUN HUANG; MENG LI; XUE‐PING ZHOU; SHU‐SHENG LIU (Molecular Ecology, 2012)
Plant‐mediated interactions between herbivorous arthropods and pathogens transmitted by herbivores are important determinants of the population dynamics of both types of organisms in the field. The role of plant defence in mediating these types of tripartite interactions have been recognized but rarely examined especially at the physiological and molecular levels. Our previous work shows that a worldwide invasive whitefly can establish mutualism with the begomovirus Tomato yellow leaf curl China virus (TYLCCNV) via crop plants. Here, we show that TYLCCNV and betasatellite co‐infection suppresses jasmonic acid defences in the plant. Impairing or enhancing defences mediated by jasmonic acid in the plant enhances or depresses the performance of the whitefly. We further demonstrate that the pathogenicity factor βC1 encoded in the betasatellite is responsible for the initiation of suppression on plant defences and contributes to the realization of the virus–vector mutualism. By integrating ecological, mechanistic and molecular approaches, our study reveals a major mechanism of the plant‐mediated mutualism between a virus and its vector. As the test plant is an important economic crop, the results also have substantial implications for developing novel strategies for management of crop viruses and the insect vectors associated with them.

Unloading the infarcted heart affect MMPs–TIMPs axis in a rat cardiac heterotopic transplantation model - Wei-jian Wang; Zi-li Meng; Yun-chang Mo; Jun-wei Liu; Cheng-chao Sun; Sheng-shou Hu; Hao Zhang (Molecular Biology Reports, 2012)

Human tissue kallikrein 1 gene delivery inhibits PDGF-BB-induced vascular smooth muscle cells proliferation and upregulates the expressions of p27Kip1 and p2lCip1 - Hui-Zhen Yu; Liang-di Xie; Peng-li Zhu; Chang-sheng Xu; Hua-jun Wang (Molecular and Cellular Biochemistry, 2012)

Chemical composition of precipitation and its sources in Hangzhou, China - Hong Xu; Xiao-Hui Bi; Yin-Chang Feng; Feng-Mei Lin; Li Jiao; Sheng-Mao Hong; Wen-Gao Liu; Xiao-Yong Zhang (Environmental Monitoring and Assessment, 2011)

A major locus qS12, located in a duplicated segment of chromosome 12, causes spikelet sterility in an indica-japonica rice hybrid - Hua Zhang; Chang-Quan Zhang; Zhi-Zhong Sun; Wen Yu; Ming-Hong Gu; Qiao-Quan Liu; Yang-Sheng Li (Theoretical and Applied Genetics, 2011)

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat - Fang Li; Xiao-Sheng Wang; Ru-Ping Dai; Jian-Yi Zhang; Xin-Fu Zhou; Wei Hao; Chang-Qi Li (Neurotoxicity Research, 2011)

Effects of exogenous hydrogen sulfide on the ascorbate and glutathione metabolism in wheat seedlings leaves under water stress - Chang-juan Shan; Sheng-li Zhang; Dong-fang Li; Yuan-zeng Zhao; Xue-liang Tian; Xin-liang Zhao; Ying-xia Wu; Xiu-ying Wei; Run-qiang Liu (Acta Physiologiae Plantarum, 2011)

Association of gene polymorphisms in prolactin and its receptor with breast cancer risk in Taiwanese women - Fan-Yun Mong; Yu-Liang Kuo; Ching-Wen Liu; Wen-Sheng Liu; Li-Ching Chang (Molecular Biology Reports, 2011)

Lentiviral shRNA silencing of CHOP inhibits apoptosis induced by cyclic stretch in rat annular cells and attenuates disc degeneration in the rats - Yue-Hui Zhang; Chang-Qing Zhao; Lei-Sheng Jiang; Li-Yang Dai (Apoptosis, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake I: Yingxiu town - Chang-Rong He; Ru Zhang; Qun Chen; Sheng-Li Han (Natural Hazards, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake II: Dujiangyan and Pengzhou City - Chang-Rong He; Qun Chen; Sheng-Li Han; Ru Zhang (Natural Hazards, 2011)

Phenotypic and Genotypic Characterization Vibrio cholerae O139 of Clinical and Aquatic Isolates in China - Bai-sheng Li; Hai-ling Tan; Duo-chun Wang; Xiao-ling Deng; Jing-diao Chen; Hao-jie Zhong; Bi-xia Ke; Chang-wen Ke; Biao Kan (Current Microbiology, 2011)

Genetic analysis of starch paste viscosity parameters in glutinous rice (Oryza sativa L.) - Chang-Jie Yan; Zhi-Xi Tian; Yu-Wei Fang; Ya-Chun Yang; Jian Li; Sheng-Yuan Zeng; Shi-Liang Gu; Chen-Wu Xu; Shu-Zhu Tang; Ming-Hong Gu (Theoretical and Applied Genetics, 2011)

Epidemic risk analysis after the Wenchuan Earthquake using remote sensing - Chunxiang Cao; Chaoyi Chang; Min Xu; Jian Zhao; Mengxu Gao; Hao Zhang; Jianping Guo; Jianghong Guo; Lei Dong; Qisheng He; Linyan Bai; Yunfei Bao; et al. (International Journal of Remote Sensing, 2010)

Analysis of Olfactory Ensheathing Glia Transplantation-Induced Repair of Spinal Cord Injury by Electrophysiological, Behavioral, and Histochemical Methods in Rats - Kai-Jun Liu; Jin Xu; Chang-Yu Yang; Han-Bo Chen; Xiang-Sheng Liu; Yong-Deng Li; Zhan-Fei Li (Journal of Molecular Neuroscience, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Viral infection of tobacco plants improves performance of Bemisia tabaci but more so for an invasive than for an indigenous biotype of the whitefly - Jian Liu; Meng Li; Jun-min Li; Chang-jun Huang; Xue-ping Zhou; Fang-cheng Xu; Shu-sheng Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Decreased levels of serum brain-derived neurotrophic factor in drug-naïve first-episode schizophrenia: relationship to clinical phenotypes - Da Chun Chen; Jing Wang; Bo Wang; Sheng Chang Yang; Chong Xi Zhang; You Lan Zheng; Yan Li Li; Ning Wang; Ke Bing Yang; Mei Hong Xiu; Thomas R. Kosten; Xiang Yang Zhang (Psychopharmacology, 2009)

Valve movement response of the freshwater clam Corbicula fluminea following exposure to waterborne arsenic - Chung-Min Liao; Sheng-Feng Jau; Chieh-Ming Lin; Li-John Jou; Chen-Wuing Liu; Vivian Hsiu-Chuan Liao; Fi-John Chang (Ecotoxicology, 2009)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

Three-class classification models of logS and logP derived by using GA–CG–SVM approach - Hui Zhang; Ming-Li Xiang; Chang-Ying Ma; Qi Huang; Wei Li; Yang Xie; Yu-Quan Wei; Sheng-Yong Yang (Molecular Diversity, 2009)

Polymorphisms in the 5′ flanking region of the insulin-like growth factor I gene are associated with growth traits in largemouth bass Micropterus salmoides - Xiao Hui Li; Jun Jie Bai; Xing Ye; Yin Chang Hu; Sheng Jie Li; Ling Yun Yu (Fisheries Science, 2009)

A novel wall-associated receptor-like protein kinase gene, OsWAK1, plays important roles in rice blast disease resistance - Hui Li; Shan-Yue Zhou; Wen-Sheng Zhao; Sheng-Chang Su; You-Liang Peng (Plant Molecular Biology, 2009)

Streptomyces mayteni sp. nov., a novel actinomycete isolated from a Chinese medicinal plant - Hua-Hong Chen; Sheng Qin; Jae-Chan Lee; Chang-Jin Kim; Li-Hua Xu; Wen-Jun Li (Antonie van Leeuwenhoek, 2009)

Association of Heart Rate Variability of the Elderly with Personal Exposure to PM1, PM1–2.5, and PM2.5–10 - Li-Te Chang; Chin-Sheng Tang; Ying-Zu Pan; Chang-Chuan Chan (Bulletin of Environmental Contamination and Toxicology, 2007)

Interleukin-1β enhances the effect of serum deprivation on rat annular cell apoptosis - Chang-Qing Zhao; Da Liu; Hai Li; Lei-Sheng Jiang; Li-Yang Dai (Apoptosis, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Effects of rosiglitazone on native low-density-lipoprotein-induced respiratory burst in circulating monocytes and on the leukocyte–endothelial interaction in cholesterol-fed rats - Long Sheng Lu; Li Man Hung; Chang Hui Liao; Chau Chung Wu; Ming Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Programmed cell death in intervertebral disc degeneration - Chang-Qing Zhao; Lei-Sheng Jiang; Li-Yang Dai (Apoptosis, 2006)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Osmotic sucrose enhancement of single-cell embryogenesis and transformation efficiency in Oncidium - Shu-Hua Li; Chang-Sheng Kuoh; Yau-Huang Chen; Hong-Hwa Chen; Wen-Huei Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

2-Benzyloxybenzaldehyde inhibits formyl peptide-stimulated increase in intracellular Ca2+ in neutrophils mainly by blocking Ca2+ entry - Jih-Pyang Wang; Ling-Chu Chang; Yu-Hsiang Kuan; Lo-Ti Tsao; Li-Jiau Huang; Sheng-Chu Kuo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Increased Risk of Developing Hepatocellular Carcinoma Associated with Carriage of the TNF2 Allele of the −308 Tumor Necrosis Factor-α Promoter Gene - Sheng-Yow Ho; Ying-Jan Wang; Hen-Li Chen; Chih-Hung Chen; Chih-Jen Chang; Po-Jen Wang; Helen H.W. Chen; How-Ran Guo (Cancer Causes & Control, 2004)

Production of two Highly Active Bacterial Phytases with Broad pH Optima in Germinated Transgenic Rice Seeds - Chwan-Yang Hong; Kuo-Joan Cheng; Tung-Hai Tseng; Chang-Sheng Wang; Li-Fei Liu; Su-May Yu (Transgenic Research, 2004)

INTERLEUKIN-8 CAN STIMULATE PROGESTERONE SECRETION FROM A HUMAN TROPHOBLAST CELL LINE, BEWO - KUAN-HAO TSUI; LING-YUN CHEN; MIAWH-LIRNG SHIEH; SHENG-PING CHANG; CHIOU-CHUNG YUAN; HSIN-YANG LI (In Vitro Cellular & Developmental Biology - Animal, 2004)

Sustainable agriculture development in saline-alkali soil area of Songnen Plain, Northeast China - Zhi-chun Wang; Qu-sheng Li; Xiu-jun Li; Chang-chun Song; Guang-xin Zhang (Chinese Geographical Science, 2003)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Analysis of DNA-Binding Activity of the JC Virus Minor Capsid Protein VP2 - Yih-Leh Huang; Meilin Wang; Wei-Chih Ou; Chiung-Yau Fung; Li-Sheng Chen; Deching Chang (Journal of NeuroVirology, 2003)

ESTABLISHMENT OF AN EFFICIENT METHOD TO QUANTIFY EMBRYO ATTACHMENT TO ENDOMETRIAL EPITHELIAL CELL MONOLAYERS - HSIN-YANG LI; SHENG-PING CHANG; CHIOU-CHUNG YUAN; HSIANG-TAI CHAO; HEUNG-TAT NG; YEN-JEN SUNG (In Vitro Cellular & Developmental Biology - Animal, 2002)

Transactivation by expression of the hepatitis B virus X protein with an inducible system - Azliyati Azizan; Yu-Sheng Cong; Ken Shain; Shih-Chang Tsai; Ya-Li Yao; Nancy Olashaw; Edward Seto (Molecular Biology Reports, 1998)